Pengaruh Motivasi Belajar, Perfeksionisme Dan Keaktifan Berorganisasi Terhadap Prokrastinasi Akademik Dengan Regulasi Diri Sebagai Variabel Moderating Di SMA Negeri 3 Medan - Cindy F Waruwu; Putri Kemala Dewi Lubis (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
An important component of high quality human resource development is education. According to Law no. 20 of 2003 Article 1 Paragraph 1, the Republic of Indonesia states that education is a serious and fundamental effort to advance learning objectives and the educational process so that students actively develop their potential to have a strong sense of identity. spirituality, self-identity control, personality, intelligence, noble character, and skills needed for oneself, society, government and country.